Fluorescence-guided surgical management of medication-related osteonecrosis of the jaws - Tomo, Saygo [UNESP]; da Cruz, Thiago Moreira; Figueira, Jéssica Araújo [UNESP]; Cunha, John Lennon Silva; Miyahara, Glauco Issamu [UNESP]; Simonato, Luciana Estevam (Elsevier, 2020)
Medication-related osteonecrosis of the jaw (MRONJ) results in progressive destruction of the jawbones, and advanced cases demand surgical intervention. The total removal of necrotic bone is required to prevent recurrence and infection. However, determining the limits between necrotic and healthy bone is a challenge. The use of fluorescence to detect tissue alterations and determine necrosis extension is a promising method to avoid inadequate bone debridement. In the literature, there are several studies and reported cases that successfully use fluorescence-guided surgery (FGS) of MRONJ. The objective of this study was to present a critical review of the literature regarding the intraoperative use of optic fluorescence to differentiate healthy and necrotic bone in MRONJ. Studies that evaluated the intraoperative use of optic fluorescence to determine the surgical margins of MRONJ were searched in Pubmed/Medline and Scopus databases using the following terms: “medication-related osteonecrosis of the jaws” and “fluorescence”. Eighteen papers describing the intraoperative use of FGS in ONJ management were selected, totalizing 218 patients. Of those 18 papers, only 5 were prospective studies, and the other 13 were isolated case reports, case series, and technical notes. The use of FGS to delimitate the resection margin of MRONJ is a promising method. There is no need for the application of exogenous fluorophore to perform FGS and the most often used light device was the VELScope® system. Further prospective studies with larger samples are still required to ascertain the fluorescence validity as a supporting method in MRONJ surgical treatment and to establish clinical protocols.
Keywords: Auto-fluorescence; Bisphosphonate; Bone; Bone fluorescence; BRONJ; DRONJ; MRONJ; Necrosis of the jaw; ONJ; Osteonecrosis; Tetracycline; Therapy; VELscope